Research on the Determination of Tort Liability for Human Damage Caused by Surgical Robots - Tang, Peng (International Journal of Social Sciences and Public Administration, 2024)
Human beings are constantly pursuing the value of their lives, thus doing constant exploration of the field of biotechnology. Surgical robots are an inevitable product of the development of science and technology to a certain stage, and have been widely used in many fields such as medical surgery and diagnosis. While liberating doctors’ hands, it also poses a brand new challenge to the legal system. Along with the surgical robots are widely used in the field of medical treatment, and its related infringement incidents gradually increased, which exposes the traditional tort theory deficiencies, but also highlights the lagging of the traditional tort law system. Compared with the general tort relationship, surgical robots involved in the tort of damage is much more complex, including the subject of tort liability confirmation, tort liability fault determination and causal relationship determination. The issue of defining the subject of tort liability has particularly triggered a heated debate in the academic community. According to the previous research and the characteristics of surgical robots, the article will discuss the issue of tort liability of surgical robots causing human damage.